PENDAMPINGAN PENGUATAN UMKM DUA PUTRI DESA PURWODADI KECAMATAN JAYALOKA - Anna Fauziah; Viktor Pandra; Maria Luthfiana (LP4MK STKIP PGRI Lubuklinggau, 2023)
This community service activity aims to provide assistance and strengthening for Dua Putri MSMEs, Purwodadi Village, Jayaloka District in marketing products processed by MSMEs using social media. The method used by the Community Service TEAM is carrying out PKM activities in two stages, namely the preparation and implementation stages. Based on the community service activities that have been carried out, the results obtained are that Dua Putri UMKM is able to market the products that have been produced outside the village of Purwodadi and its surroundings, management is not yet neatly organized, therefore assistance is provided to increase understanding of the importance of social media as a tool. marketing as well as providing insight into the importance of innovating in product packaging starting from creating logos, packaging to the ready-to-sell stage and providing appropriate management training.